ANALISIS SEDIMENTASI LAGUNA SEGARA ANAKAN DENGAN PEMODELAN NUMERIK ANGKUTAN SEDIMEN KOHESIF - Irham Adrie Hakiki; Leo Eliasta Sembiring; Cahyo Nur Rahmat Nugroho (JURNAL TEKNIK HIDRAULIK, 2021)
Sagara Anakan Lagoon has been continuously receded caused by the high sedimentation rate. The deposited sediment volume was predicted to be around 1 million m3/year. This phenomenon, if not treated will harm the existing ecosystem and also could cause many kinds of its native biota extinct. Engineering could be applied to prevent it. However, the transport and sedimentation pattern must be known for it to be effective.  Silting in Sagara Anakan Lagoon simulated by using MIKE21 numerical model which could simulate sediment transport in 2D horizontal scheme. The deposited sediment, mainly consisted of mud, so the model must be capable for simulating cohesive sediment transport. Model is set to simulate one year of morphological event which reached with the usage of time speed up acceleration factor. Model calibrated to be able to simulate a deposition event in the order of one million m3/year. Model calibrated by tuning critical bed shear stress for deposition   and erosion  parameters as a base for sensitivity analysis. Model result shown that the sedimentation in Sagara Anakan Lagoon is caused by asymmetry of flood and ebb current. Major siltation happened around the delta with the maximum and mean observed bed change are approximately 0.6 m and 0.16 m respectively. The setup for this model could be used as a base model for planning an engineering approach for controlling sediment in Sagara Anakan Lagoon.Keywords: Numerical model, cohesive sediment, mud transport, estuary modellingKata Kunci: Model numerik, sedimen kohesif, transpor lumpur, pemodelan estuari